2018
DOI: 10.24198/pjd.vol30no3.19275
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of crown width, length, width/length ratio of maxillary anterior teeth between male and female dental students

Abstract: Introduction: Crown width and crown length provides significant information on human evolution as well as in forensic and clinical dentistry. The width-to-length ratio or individual tooth proportion (ITP) of maxillary anterior teeth considered as an important factors for dental aesthetics and harmonic teeth arrangement. The goal of this research is to establish if there is any significant difference in crown width, length, width/length ratio of permanent maxillary anterior teeth between male and female student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…All probands were selected from the Caucasian population. Analyses of the CCL and WAG were performed on the following teeth: the maxillary and mandibular canines (13,23,33,43) and the maxillary and mandibular central incisors (11,21,31,41). Since this was an observational cross-sectional study, there was no predetermined sample size.…”
Section: Participantsmentioning
confidence: 99%
“…All probands were selected from the Caucasian population. Analyses of the CCL and WAG were performed on the following teeth: the maxillary and mandibular canines (13,23,33,43) and the maxillary and mandibular central incisors (11,21,31,41). Since this was an observational cross-sectional study, there was no predetermined sample size.…”
Section: Participantsmentioning
confidence: 99%
“…10 As a result, because it exhibited the least change across genders, the crown width-to-length ratio was recognized as the most consistent standard. 19,27…”
Section: Discussionmentioning
confidence: 99%
“…Maxillary anterior teeth, being the most prominent ones, are paramount to the restoration of anterior dental esthetics as well as overall facial esthetics [ 5 ]. Selection of appropriate crown length and width is essential to creating esthetically pleasing smiles.…”
Section: Introductionmentioning
confidence: 99%
“…Magne et al, in contrast, utilized extracted teeth to measure CWHR and observed mean ratios of 78% for central incisors and 73% each for lateral incisors and canines [ 9 ]. While Chu [ 10 ] reported a CWHR of 78% for all maxillary anterior teeth using “Chu's esthetic proportion gauge,” Shahid et al [ 11 ] and Yuan et al [ 5 ] utilized digital calipers to measure the dimensions of maxillary teeth and reported significant differences only in terms of crown widths and height between males and females and not in CWHR. With advancements in digital dentistry, 3D digital models and software are now being used for easier and faster measurements of dental clinical parameters [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%